2014
DOI: 10.1177/2053434514556686
|View full text |Cite
|
Sign up to set email alerts
|

The underlying challenges of coordination of chronic care across Europe

Abstract: An effective response to the rising burden of chronic disease requires a health system environment that is conducive to implementing structured, integrated approaches to chronic disease prevention and management. This study presents some of the reported factors hindering the successful implementation of chronic care approaches in six European healthcare systems and focuses on processes to address these. We conducted 42 semi-structured interviews with key informants in The Netherlands and Spain, representing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…As in previous studies [ 32 , 33 ], these supervisors and case managers recognized the benefits of using case management as a vehicle for overcoming system fragmentation and for facilitating optimal service delivery to women and their families, and sought to link clients to available services in a timely manner. They clearly also strove to meet the program rules, guidelines and timelines, and respond to the evolving operating environment through rapid demographic shifts and gentrification [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 95%
“…As in previous studies [ 32 , 33 ], these supervisors and case managers recognized the benefits of using case management as a vehicle for overcoming system fragmentation and for facilitating optimal service delivery to women and their families, and sought to link clients to available services in a timely manner. They clearly also strove to meet the program rules, guidelines and timelines, and respond to the evolving operating environment through rapid demographic shifts and gentrification [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 95%
“…Our respondents indicated that ACOs have put PSP in charge of care coordination and logistical help in various settings. 28 While the model in which multiple providers take care of the same patient is a problem that plagues health care in many countries, 29 PSP could connect disparate parts of the system while focusing on patients' needs. However, reaping the benefits of improved coordinated care may require physicians to relinquish some authority to PSP, and it is unclear whether physicians will embrace such change.…”
Section: Discussionmentioning
confidence: 99%
“…2 The authors emphasize cross-disciplinary collaboration and designing patient centric care, and the need for systemic wide support. 2…”
Section: Introductionmentioning
confidence: 99%
“…1 In a recent article in the International Journal of Care Coordination, it was concluded that barriers to improve care coordination for the chronically ill include: (a) a continued focus on complications management and a failure to integrate risk minimization and disease prevention along the spectrum of care; (b) care fragmentation acting as a barrier to better coordination; (c) a mismatch between intent, at national level, to enhance coordination and integration, and ability at regional or local level to translate these ambitions into practice; and (d) a lack of structures suitable to promote proactive engagement with patients in the management of their own condition. 2 The authors emphasize cross-disciplinary collaboration and designing patient centric care, and the need for systemic wide support. 2 In Australia, 3.3 million people suffer from general arthritis, of which about 450,000 are people with rheumatoid disease (including 5000 children), which is the most severe form of arthritis involving a lifelong painful chronic condition associated with very serious health consequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation